PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN CONTEXTUAL TEACHING AND LEARNING SISWA SEKOLAH DASAR - Juliana, Juliana; Marli, Suhardi; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to improve student learning outcomes in the learning of Social Sciences using Contextual Teaching And Learning in fourth grade students of State Elementary School 01 Sebetung Lit up. Data collection techniques used in this study are observation techniques, document scrutiny techniques. Data collection tools in this study are observation sheets and document observation sheets.The results of the study on the implementation of learning design (RPP) from the average score of the cycle I 2.78, cycle II average score of 3.71, and the average score of cycle III 3.88.research on the implementation of learning from the first cycle average score of 3.72, cycle II an average score of 3.8 and the third cycle average score of 3.97, always having an increase due to the implementation of learning using Contextual Teaching And Learning.The percentage of completeness of student learning outcomes increased by 26.09% from 39.13% in Cycle I to 65.22% in Cycle II, while the increase in cycles II and cycle III was 34.78% from 65.22% in cycle II becomes 100% in cycle III. In conclusion there is an increase in student learning outcomes in the learning of Social Sciences by using Contextual Teaching And Learning in class 1V SD Negeri 01 Sebetung Menyala Bengkayang Regency. Keywords : Contextual Teaching And Learning, Improving Learning Results, Social Sciences